2021
DOI: 10.3390/jcm10081720
|View full text |Cite
|
Sign up to set email alerts
|

Superior Orbicularis Oris Muscle Activity in Children Surgically Treated for Bilateral Complete Cleft Lip and Palate

Abstract: The aim of this cross-sectional study was to evaluate the electromyographic activity of the superior orbicularis oris muscle both in children surgically treated for bilateral complete cleft lip and palate (BCCLP) as well as in subjects without BCCLP. The study comprised 77 children aged 6.6 to 12.5 years. All the patients with clefts had previously undergone lip and palate surgery. The upper lip electromyographic (EMG) assessments were made with a DAB-Bluetooth device (Zebris Medical GmbH, Germany) at rest, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 47 publications
0
12
0
4
Order By: Relevance
“…They suggested that individuals with lip incompetence have difficulty chewing due to an inability to achieve lip seal, which affects their masticatory function. What is more, Szyszka-Sommerfeld et al [ 15 ] compared the electromyographical values of the SOO muscle during saliva swallowing in children with congenital anomalies, such as bilateral complete cleft lip and palate (BCCLP) and an abnormal lip seal with those of BCCLP children and lip incompetence. They observed significantly higher EMG potentials in children with BCCLP and an abnormal lip seal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that individuals with lip incompetence have difficulty chewing due to an inability to achieve lip seal, which affects their masticatory function. What is more, Szyszka-Sommerfeld et al [ 15 ] compared the electromyographical values of the SOO muscle during saliva swallowing in children with congenital anomalies, such as bilateral complete cleft lip and palate (BCCLP) and an abnormal lip seal with those of BCCLP children and lip incompetence. They observed significantly higher EMG potentials in children with BCCLP and an abnormal lip seal.…”
Section: Discussionmentioning
confidence: 99%
“…During the EMG recordings the subjects’ sat in a dentist’s chair with the head in a natural head position [ 14 ]. The electrodes were arranged as follows: An the superior orbicularis oris (SOO) muscle—along the line from the lip commissure to the nose (the subnasal point); the inferior orbicularis oris (IOO) muscle—along the line from the lip commissure to the mandibular midline; and the reference electrode—lower and behind the right ear [ 15 , 16 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral processing and its related quantitative devices (Geckili et al, 2012; Hongama et al, 2012; Szyszka‐Sommerfeld, Machoy, Wilczyński, Lipski, & Woźniak, 2021; Thymi, Verhoeff, Visscher, & Lobbezoo, 2020; Ueki et al, 2012; Watts, 2013; Yamaguchi, Mikami, Saito, Okada, & Gotouda, 2018)…”
Section: Quantitative Parameters and Methods Of Oral Processingmentioning
confidence: 99%
“…F I G U R E 3 Oral processing and its related quantitative devices (Geckili et al, 2012;Hongama et al, 2012;Szyszka-Sommerfeld, Machoy, Wilczy nski, Lipski, & Woźniak, 2021;Thymi, Verhoeff, Visscher, & Lobbezoo, 2020;Ueki et al, 2012;Watts, 2013;Yamaguchi, Mikami, Saito, Okada, & Gotouda, 2018) The device used in the above study can only detect the closing force in the vertical direction. However, lip closure is not onedimensional vertical extrusion of two planes but multi angle extrusion of two-dimensional plane, besides, the volume of lip-closing force in different directions is different.…”
Section: Lip-closing Force Detection Devicementioning
confidence: 99%